Žilvinas Kempinas - Watkins, Jonathan 1957-; Watkins, Jonathan 1957- (Ikon Gallery, 2016)
This catalogues accompanies the '‌ilvinas Kempinas' exhibition at Ikon Gallery. Comprising a number of installations it is characteristically elemental, representing and embodying natural phenomena such as light and the circulation of air, with an emphasis on movement made by both visitors and kinetic works in the exhibition. 00Exhibition: Ikon Gallery, Birmingham, United Kingdom (23.09.-27.11.2016)
Keywords: Kempinas, Žilvinas -- 1969-; Installation -- Kunst; Videokunst; Kempinas, Zilvinas 1969- / Exhibitions; Ausstellungskatalog; Ausstellungskatalog -- Ikon Gallery -- 23.09.2016-27.11.2016 -- Birmingham; Bildband